2006
DOI: 10.1152/ajpregu.00684.2005
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis and inflammatory insults downregulate IGFBP-5, but not IGFBP-4, in skeletal muscle via a TNF-dependent mechanism

Abstract: The purpose of the present study was to determine whether catabolic stimuli that induce muscle atrophy alter the muscle mRNA abundance of insulin-like growth factor binding protein (IGFBP)-4 and -5, and if so determine the physiological mechanism for such a change. Catabolic insults produced by endotoxin (LPS) and sepsis decreased IGFBP-5 mRNA time- and dose-dependently in gastrocnemius muscle. This reduction did not result from muscle disuse because hindlimb immobilization increased IGFBP-5. Continuous infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 65 publications
2
23
0
1
Order By: Relevance
“…In fish muscle, only positive effects of igfbp5 have been described, showing that amino acids alone, as well as the combination of amino acids and Igf1 or Igf2, promote igfbp5 expression in differentiated myogenic cells (Bower & Johnston 2010), supporting the fact that pro-anabolic molecules (i.e. Gh and Igf1) increase igfbp5 expression, as was previously shown in mammals (Lang et al 2006). In the fine flounder, igfbp5 expression decreases under nutritional catabolic periods of fasting and increases during favorable nutritional anabolic periods of refeeding, similar to previous reports in other fish species, supporting the idea that Igfbp5 has a positive role in muscle , Bower et al 2008, Macqueen et al 2011.…”
Section: Transcriptional Regulation Of Igfbps In the Skeletal Muscle supporting
confidence: 64%
See 1 more Smart Citation
“…In fish muscle, only positive effects of igfbp5 have been described, showing that amino acids alone, as well as the combination of amino acids and Igf1 or Igf2, promote igfbp5 expression in differentiated myogenic cells (Bower & Johnston 2010), supporting the fact that pro-anabolic molecules (i.e. Gh and Igf1) increase igfbp5 expression, as was previously shown in mammals (Lang et al 2006). In the fine flounder, igfbp5 expression decreases under nutritional catabolic periods of fasting and increases during favorable nutritional anabolic periods of refeeding, similar to previous reports in other fish species, supporting the idea that Igfbp5 has a positive role in muscle , Bower et al 2008, Macqueen et al 2011.…”
Section: Transcriptional Regulation Of Igfbps In the Skeletal Muscle supporting
confidence: 64%
“…Despite some reports that have shown that IGFBP5 inhibits cell proliferation and differentiation in muscle (Ewton et al 1998), this negative role has been questioned , showing abundant evidence that points out a positive role in muscle growth (Awede et al 2002, Lang et al 2006, Bower et al 2008, Ren et al 2008, Bower & Johnston 2010, Macqueen et al 2011. Particularly, IGFBP5 promotes muscle differentiation; its absence impairs myogenesis (Ren et al 2008), and its expression increases with muscle hypertrophy and decreases during muscle atrophy (Awede et al 2002, Lang et al 2006. In fish muscle, only positive effects of igfbp5 have been described, showing that amino acids alone, as well as the combination of amino acids and Igf1 or Igf2, promote igfbp5 expression in differentiated myogenic cells (Bower & Johnston 2010), supporting the fact that pro-anabolic molecules (i.e.…”
Section: Transcriptional Regulation Of Igfbps In the Skeletal Muscle mentioning
confidence: 99%
“…Elevated TNFα concentration generates an increase in the activity of ubiquitin-conjugated protein degradation and inhibition of insulin / IGF mediated protein synthesis (GarciaMartinez et al 1993;Garcia-Martinez et al 1994;Fernandez-Celemin et al 2002;Plomgaard et al 2005;Williamson et al 2005;Lang et al 2006). Furthermore, TNFα has also been shown to negatively affect anabolic processes by destabilising myogenic differentiation and altering transcriptional activity (Langen et al 2004;Vashisht Gopal et al 2006).…”
Section: Tumor Necrosis Factor Alpha (Tnfα)mentioning
confidence: 99%
“…Furthermore, TNFα has also been shown to negatively affect anabolic processes by destabilising myogenic differentiation and altering transcriptional activity (Langen et al 2004;Vashisht Gopal et al 2006). Suppression of the insulin / IGF signalling pathway by TNFα has been shown to induce insulin resistance via impaired phosphorylation of IRS-1 and the AKT substrate AS160 kDa (del Aguila et al 1999;de Alvaro et al 2004;Plomgaard et al 2005), and suppress protein synthesis through a decrease in IGF-1 and IGF-binding protein gene expression, subsequently inhibiting elongation initiation and mRNA translational efficiency in skeletal muscle (Lang et al 2002;Williamson et al 2005;Lang et al 2006). Early studies using intravenous administration of TNFα revealed a significant time-dependent increase in free ubiquitin and ubiquitin gene expression highlighting the role of TNFα with regard to elevated muscle proteolysis (GarciaMartinez et al 1993;Garcia-Martinez et al 1994).…”
Section: Tumor Necrosis Factor Alpha (Tnfα)mentioning
confidence: 99%
“…The dose of TNF BP and timing of the initial injection were chosen based on the peak plasma TNF levels (60-80 pg/mL) 4 h after induction of sepsis in this model (26) and previous pharmacokinetic studies (data not shown) demonstrating the plasma concentrations of TNF BP remain above 500 ng/mL for at least 12 h after subcutaneous injection of 1 mg/kg TNF BP . Therefore, by injecting the TNF BP 4 h prior to induction of sepsis, we were assured of relatively high concentrations of TNF BP throughout the septic insult.…”
Section: Experimental Protocolsmentioning
confidence: 99%